The Effect of Night Sky Quality in the Glanggang Tourism Village Area in Order to Diversify Astronomy Tourism - A Yasinta; Morshed Hadwan; Sutrisno Sutrisno; Mamadou Simina Dramé; Dessalegn Ayehu Mekuriaw (Tinta Emas Publisher, 2025)
Indonesia's economic sector is experiencing rapid growth with the development of tourism. Eco-friendly tourism introduced with the resource of dark skies without light is called astronomy tourism. The brightness of the night sky is closely related to determining the location of astronomy tourism. Measuring the brightness of the night sky plays an important role for observing celestial objects. The research was conducted in Glanggang Village, Pakisaji District, Malang Regency. This research is useful to provide information on whether or not the place is suitable as an astronomy tourism location, besides adding to the attractiveness of tourism by enjoying the beauty of celestial objects. The method used in measuring sky brightness is the Sky Quality Meter type SQM-L. Observations were made for 8 days with a time duration of every 15 minutes. The data is analyzed using the correlation between time and sky brightness value using MPSAS (Magnitude per Square Arc Second) unit. Based on the observation, the highest sky brightness value is 21.4 MPSAS, indicating that the sky brightness value at night is quite high, so light pollution is quite low. According to the results of the observation data, it is concluded that Glanggang Village can be used as an astronomy tourism location.